A heurística do temor em Hans Jonas: diálogo com a ficção científica em Frankenstein e A Pele que Habito - Santos, Adriana Karla Pereira dos (2025)
This study aims to promote a discussion on the “heuristic of fear,” proposed by Hans Jonas in his work “The Imperative of Responsibility,” as a central principle in Jonasian ethics to awaken human beings to their responsibility in the face of technological advancements and their impacts on society and the planet. The research is based on a bibliographic review of Jonas’ work and commentators, in addition to an analysis of two science fiction works: the literary classic “Frankenstein” and the film “The Skin I Live In.” Both works explore the issue of responsibility in science and the dangers of unbridled ambition, illustrating the need for ethics to guide technological development and ensure the sustainability of human life. The heuristic of fear, as a guide for responsible action, impels us to consider the potential consequences of technological interventions and to act with prudence and caution. In the face of the power of modern technoscience, fear, as a rational concern, should guide human actions and prevent the realization of catastrophic scenarios. The study concludes that the heuristic of fear, as an ethical principle, can contribute to the discussion on technoscientific advancement and the future of authentic human life. The ability to anticipate dangers and act responsibly is fundamental to avoid the degradation of life on the planet and to guarantee the permanence of a just and sustainable society.